OPTIMALISASI KINERJA KARYAWAN MELALUI SELF EFFICACY, PENGEMBANGAN KARIR, DAN KEPEMIMPINAN TANSFORMASIONAL - sumartik sumartik sumartik; Lisa Rachmadiyah; Dewi Andriani (Departemen Manajemen, 2023)
This study aims to determine the effect of self efficacy, career development, and transformational leadership on employee performance at Dinas Koperasi dan Usaha Mikro Kabupaten Sidoarjo, both in partial and simultant. This research is a type of quantitative reseacrh with descriptive approach, and using likert scale analysis tools of 1-5 and multiple linear regression analysis with the help of SPSS 24 software. Data collection techniques using questionnaires are distributed via the google form link. The population in this study is 85 employees of Dinas Koperasi dan Usaha Mikro Kabupaten Sidoarjo and the sampling technique with a census techniques, namely as many as 85 respondents. The results of this study indicate that self efficacy, career development, and transformational leadership simultaneously and partially have a positive and significant effect on employee performance. From the results of the coefficient of determination it is known that the contribution of self efficacy, career development, and transformational leadership variables affects the employee performance variable which is equal to 54,3% and the remaining 45,7% is influenced by other variables that are not used in this study.